The Influence of Transformational Leadership and Lecturer Motivation on Lecturer Performance Through Tacit Knowledge Sharing at the Institut Sains dan Teknologi Terpadu Surabaya - Pandu Agung Setiawan (Journal of Social Research, 2023)
The Industrial Revolution 4.0 era created an environment known as VUCA (Volatility, Uncertainty, Complexity, and Ambiguity) as a result of rapid technological advances. VUCA impacts how people make decisions, plan, manage risk, drive change and solve problems in an increasingly information-hungry society. This change also requires leaders to think faster, process information in a short time, and have a clear vision. Higher education leaders need to provide good control to improve lecturer performance in preparing students for an increasingly complex world of work. Improving soft skills for students is a big challenge for university lecturers. Therefore, higher education leaders, such as at the Institut Sains dan Teknologi Terpadu Surabaya  (ISTTS), must develop a transformational leadership management system that supports lecturer motivation, both intrinsic and extrinsic, and encourages the sharing of tacit knowledge. This research uses quantitative methods by collecting data through face-to-face questionnaires. The results of the descriptive analysis show that the role of leadership, lecturer motivation, and tacit knowledge sharing have a significant effect on lecturer performance, which in turn influences the overall performance of the institution. This research also found that the role of transformational leadership does not directly influence lecturer performance but through the mediation of tacit knowledge sharing. Lecturer motivation, on the other hand, has a significant influence both directly and through tacit knowledge sharing. Tacit knowledge sharing also has a positive and significant impact on lecturer performance. These findings confirm that transformational leadership and lecturer motivation have an impact on lecturer performance through sharing tacit knowledge.